Análise técnica da integração de sistemas fotovoltaicos conectados à rede nas edificações da Fundação Universidade Federal de Mato Grosso do Sul - Pereira, Priscila Martins Mateus de Oliveira (2021)
Spending on electricity in public agencies is high, especially on the Ministry of Education, which led the ranking of expenditures by public agencies in 2017 (R$ 702.5 million). One option to mitigate this cost is through distributed generation. In this modality, the use of photovoltaic systems has been growing rapidly and is a viable option since Brazil has high levels of solar radiation. The objective of this work was to technically evaluate the generation of electric energy through photovoltaic systems connected to the grid and integrated in the building roofs of the Cidade Universitária campus of the Federal University of Mato Grosso do Sul Foundation, in the city of Campo Grande, MS. This campus is subdivided into four sectors. Sector 1 is responsible for 62% of total consumption (4,167.1 MWh) and Sectors 2, 3 and 4 consume annually 870 MWh, 1,043 MWh and 661 MWh, respectively. The integration of photovoltaic systems in building roofs was analyzed. Three technologies of photovoltaic modules (multi-Si, mono-Si and CdTe) and two Inverter Loading Rates for each system were considered. The simulations were made using System Advisor Model (SAM) and the performance of the photovoltaic systems was analyzed using the PR and yield indicators. Systems with mono-Si technology resulted in the greatest integration potential (5,253.8 kW) and, therefore, generated the greatest amount of electrical energy (6,957.3 MWh) among all technologies. However, the performance of systems with CdTe was the highest (yield and PR weighted of 1,360 kWh/kW and 0.75, respectively), proving to be the most suitable technology for photovoltaic systems in Campo Grande, MS in terms of performance. The CdTe photovoltaic cells showed better productivity on the day of high temperature and high levels of solar irradiation, but on the day with mild temperature and medium solar irradiation their performances were like those of the multi-Si photovoltaic cells. No significant relationship was observed between Inverter Loading Rates and resulting performance. Buildings with sub-arrays in the North and South quadrants have greater differences between their sub-array yields than those observed in buildings with sub-arrays in the East and West. In subarrays with azimuthal angles in the North quadrant, the surfaces with higher slopes resulted in less losses, while for subarrays with azimuthal angles in the South quadrant, this occurred in the smallest slopes. The photovoltaic systems in Sectors 2 and 3 generated more electricity than the annual consumption, resulting in generation surpluses. In turn, in Sectors 1 and 4 there was a deficit of electricity, with partial compensation of consumption in solar time in Sector 1 and total compensation in the same period in Sector 4. The excess energy in Sectors 2 and 3 was used to reduce the generation deficits of the Sectors 1 and 4. The greater integration potential of mono-Si systems resulted in greater compensation for energy consumed on campus (95%), requiring 281 kW more of installed power for the UFMS to be considered electrically self-sufficient.